2014
DOI: 10.3109/15360288.2014.938883
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Challenges in Cancer Pain Management: A Systematic Review of Methadone

Abstract: The proven therapeutic efficacy of methadone in cancer pain is hindered by a challenging pharmacokinetic-pharmacodynamic profile, considerable interpatient variation, and increasing concern about the complexities of dosing. The objective of this study was to assess the evidence for the use of methadone in cancer pain management. The authors conducted a systematic literature search for randomized controlled trials (RCTs) published post the 2007 Cochrane review of methadone in cancer pain. Trial quality was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…4 When no difference between nociceptive and neuropathic pain was made, no difference in pain relief between morphine and methadone could be observed. A more recent systematic review, 23 based on 4 RCTs published after the 2007 Cochrane review, showed no difference in effectiveness between methadone compared to other strong opioids in 2 RCTs. 20,24 Two other RCTs used in this systematic review evaluated the effect of opioid rotation to methadone: in one study no conclusion on the efficacy of methadone in treatment of cancer pain could be presented due to the number of dropouts, 25 and the other reported a decrease in pain intensity switching from morphine to methadone and a patient preference for methadone.…”
Section: Discussionmentioning
confidence: 99%
“…4 When no difference between nociceptive and neuropathic pain was made, no difference in pain relief between morphine and methadone could be observed. A more recent systematic review, 23 based on 4 RCTs published after the 2007 Cochrane review, showed no difference in effectiveness between methadone compared to other strong opioids in 2 RCTs. 20,24 Two other RCTs used in this systematic review evaluated the effect of opioid rotation to methadone: in one study no conclusion on the efficacy of methadone in treatment of cancer pain could be presented due to the number of dropouts, 25 and the other reported a decrease in pain intensity switching from morphine to methadone and a patient preference for methadone.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies suggest cardiovascular effects, such as prolongation of the QT interval or torsades de pointes. Given its long and variable half-life, potential interactions with several drugs, variability in conversion factors and the association with prolongation of the QT interval make methadone a drug with specific safety requirements [44].…”
Section: • Methadonementioning
confidence: 99%
“…Three of these studies focus only on cancer-related pain and lack comprehensiveness, as they each include different RCTs. 20,38,47 Moreover, a recently published systematic review by D'Souza et al evaluates the use of methadone in postoperative pain control. 12 Several RCTs involving postprocedural pain are omitted from inclusion in the aforementioned review, however, and there is need for the evaluation of methadone's safety profile.…”
Section: Introductionmentioning
confidence: 99%